1993
DOI: 10.1007/bf00051714
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukemia in the vicinity of Canadian nuclear facilities

Abstract: An ecologic study was conducted to determine whether leukemia rates among children born to mothers residing in the vicinity of Ontario (Canada) nuclear facilities differed from the provincial average. Childhood leukemia mortality and incidence ratios for the period 1950 to 1987 were examined for five regions within 25 km of a nuclear facility. The nuclear facilities included a research development facility, a uranium refinery, a uranium mining and milling facility, and two nuclear-power generating stations. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…Several studies have systematically examined the evidence relating to all of a country's nuclear installations. Mortality studies in the USA (Jablon et al, 1991), Canada (McLaughlin et al, 1993), France (Hattchouel et al, 1995), Spain (Lopez-Abente et al, 1999) and Japan (Iwasaki et al, 1995), and incidence studies in England and Wales (Bithell et al, 1994), Scotland (Sharp et al, 1996), Germany (Michaelis et al, 1992;Kaatsch et al, 1998), Sweden (Waller et al, 1995), Canada (McLaughlin et al, 1993) and the USA (Jablon et al, 1991) found no statistical evidence of an excess of leukaemia among children living around nuclear sites. In France, despite indications of increased incidence for certain combinations of age groups and geographical areas, extensive investigation of the La Hague site (Viel and Richardson, 1990;Viel et al, 1993Viel et al, , 1995Pobel and Viel, 1997;Guizard et al, 2001;Boutou et al, 2002) finally yielded, as for the Marcoule site (Bouges et al, 1999), no evidence of a significant excess of cases of childhood leukaemia.…”
mentioning
confidence: 99%
“…Several studies have systematically examined the evidence relating to all of a country's nuclear installations. Mortality studies in the USA (Jablon et al, 1991), Canada (McLaughlin et al, 1993), France (Hattchouel et al, 1995), Spain (Lopez-Abente et al, 1999) and Japan (Iwasaki et al, 1995), and incidence studies in England and Wales (Bithell et al, 1994), Scotland (Sharp et al, 1996), Germany (Michaelis et al, 1992;Kaatsch et al, 1998), Sweden (Waller et al, 1995), Canada (McLaughlin et al, 1993) and the USA (Jablon et al, 1991) found no statistical evidence of an excess of leukaemia among children living around nuclear sites. In France, despite indications of increased incidence for certain combinations of age groups and geographical areas, extensive investigation of the La Hague site (Viel and Richardson, 1990;Viel et al, 1993Viel et al, , 1995Pobel and Viel, 1997;Guizard et al, 2001;Boutou et al, 2002) finally yielded, as for the Marcoule site (Bouges et al, 1999), no evidence of a significant excess of cases of childhood leukaemia.…”
mentioning
confidence: 99%
“… nine were descriptive ecological studies that compared the rates of all causes of death, of cancer incidence, and of birth defects among Port Hope residents with the general population of Ontario, similar communities, and the rest of the population of Canada [24][25][26][27][28][29][30][31][32][33][34][35];  two were case-control studies, one investigated the relationship between lung cancer and residential radon exposure in homes [36,37], the second one studied if there was an association between childhood leukaemia and father's occupational exposure to ionizing radiation before the child's conception [38]; and two were cohort studies on Eldorado workers [39,40] and provided data on approximately 50 years of mortality and 30 years of cancer incidence for Port Hope's radium and uranium refining and processing facility workers. The epidemiological studies provided no evidence of excess kidney disease or bone cancer.…”
Section: Moderate To Highmentioning
confidence: 99%
“…Les mêmes conclusions sont obtenues quand la localisation des cas est déter-minée à partir du lieu de naissance et quand la localisation des cas est déterminée à partir du lieu de diagnostic. Enfin, le risque observé est similaire avant et après démar-rage de la centrale de Pickering (Clarke et al, 1991 ;McLaughlin et al, 1993).…”
Section: Canadaunclassified